Effect of LSVT® BIG on standing balance in a Parkinson's patient: A case report. (5th September 2021) - Iwai, Masanobu; Koyama, Soichiro; Takeda, Kazuya; Hirakawa, Yuichi; Motoya, Ikuo; Kumazawa, Nobuhiro; Sakurai, Hiroaki; Kanada, Yoshikiyo; Kawamura, Nobutoshi; Kawamura, Mami; Tanabe, Shigeo
Abstract: Background and Purpose: There are no reports regarding the effect of Lee Silverman Voice Treatment® BIG (LSVT® BIG) on standing balance ability evaluated using quantitative assessment. This case report aimed to describe and evaluate the influence of LSVT® BIG on the center of pressure (COP) trajectory in a patient with Parkinson's disease (PD). Methods: Although this paper focused on one case, quantitative assessment on the effect of LSVT® BIG on standing balance ability was performed. A 67‐year‐old woman patient diagnosed with PD at age 59, with a Hoehn and Yahr stage 3 disability severity, underwent a 4‐weeks supervised LSVT® BIG program. The total distances of the COP trajectory (two‐dimensional [2D] horizontal plane, anterior‐posterior [AP] direction, and medial‐lateral [ML] direction), and the mean COP velocity for each direction, postural stability, and posture subsections of the Unified Parkinson's Disease Rating Scale (UPDRS) Part 3 were assessed at pre‐ and post‐intervention. Results: The total distances of the COP trajectory, mean COP velocities, and scores of postural stability and posture subsections of the UPDRS Part 3 improved after intervention (from 124.6 to 76.6 cm [2D], 89.4 to 57.7 cm [AP], 77.4 to 38.5 cm [ML]; 4.0 to 2.6 cm/s [2D], 3.0 to 1.9 cm/s [AP], 2.6 to 1.3 cm/s [ML]; and 3 to 0, and 3 to 2, respectively). Discussion: LSVT® BIG may be effective in improving the total distance of the COP trajectory, mean COP velocity, and both postural stability and posture subsections of the UPDRS Part 3 in the presented PD case.